2017
DOI: 10.1056/nejmoa1613125
|View full text |Cite
|
Sign up to set email alerts
|

KIT Inhibition by Imatinib in Patients with Severe Refractory Asthma

Abstract: BACKGROUND Mast cells are present in the airways of patients who have severe asthma despite glucocorticoid treatment; these cells are associated with disease characteristics including poor quality of life and inadequate asthma control. Stem cell factor and its receptor, KIT, are central to mast-cell homeostasis. We conducted a proof-of-principle trial to evaluate the effect of imatinib, a KIT inhibitor, on airway hyper-responsiveness, a physiological marker of severe asthma, as well as on airway mast-cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 37 publications
(38 reference statements)
1
121
0
Order By: Relevance
“…However, there is a possibility that we will obtain some insight into this question with the use of therapies that target mast cells in humans. For example, blocking the effects of c‐KIT in mast cells by using the tyrosine kinase inhibitor, imatinib, produces a profound decrease in mast cells in patients with chronic myeloid leukemia (CML) and severe asthma . Thus far, a small study with 23 CML patients showed no increase in the frequency of severe bacterial or fungal infections after treatment with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a possibility that we will obtain some insight into this question with the use of therapies that target mast cells in humans. For example, blocking the effects of c‐KIT in mast cells by using the tyrosine kinase inhibitor, imatinib, produces a profound decrease in mast cells in patients with chronic myeloid leukemia (CML) and severe asthma . Thus far, a small study with 23 CML patients showed no increase in the frequency of severe bacterial or fungal infections after treatment with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this argument, long-term treatment with imatinib caused a profound MC deficiency in mice and patients with PH + CML 89 . Furthermore, a recent study examined the clinical utilization of Imatinib for treatment of severe refractory asthmatic patients and demonstrated that Imatinib had excellent efficacy, reducing mast cell counts and activation and asthma symptoms 90 .…”
Section: Discussionmentioning
confidence: 99%
“…5), in the present study, we observed significant mast cell infiltration of the airways that was unaffected by Dex. In a study just published, treatment of severe asthmatics with imatinib -which targets KIT, a molecule expressed by mast cells -reduced AHR, even though mast cells numbers were reduced (but not eliminated) only after prolonged treatment (54). Mast cells are known to be long-lived, and given that they can contribute to AHR, the potential for type 1 inflammation to promote their accumulation in the airways highlights another detrimental effect of IFN-γ in establishment of SA and the poor response of this disease state to CS.…”
Section: Discussionmentioning
confidence: 99%